The Emperor's Last Campaign : A Napoleonic Empire in America - Ocampo, Emilio, 1963- (Book collections on Project MUSE., 2009)
"Napoleon's last campaign didn't end at Waterloo. After that fateful day on June 1815, hundreds if not thousands of veterans of Napoleon's army emigrated to America. Many went farther south and joined the rebels fighting for independence in the Spanish colonies, from Mexico to Buenos Aires. The Bonapartists roiled the Western World as they sought fortune, fame, and glory in the expanding United States and in the tumultuous Spanish Americas suffering from repression and civil disorder, and even in the states of Europe. Among them were Lord Thomas Cochrane, Sir Robert Wilson, Charles Lallemand, and Michel Brayer, some of the most interesting characters of the Napoleonic era. This is the first full-length examination of the Bonapartists who emigrated from France after Napoleon's defeat and exile, who formed a loose confederation with adventurers and romantics, and who contemplated a new empire in the Western Hemisphere. The scheme had the support and encouragement of the fallen emperor himself and his brother Joseph, former King of Spain. Emilio Ocampo has examined archives on three continents and sources in several languages to ferret out the evidence - a monumental task considering that conspirators tried to leave no evidence of their plans, and that a failed plot, like failure in general, leaves few claimants. Ocampo reinterprets Latin American independence as an international event that drew in all the states of the Atlantic basin. By illuminating the complex connections between the shattered France of the Bourbon restoration; new radicals in a Britain inspired by the French Revolution; Napoleon in exile at St. Helena; the United States, where home-grown adventurers and French emigres alike saw opportunity; and, the collapsing Spanish colonial empire, where revolutionaries were allying themselves with the veterans of Napoleon's Grande Armee, Ocampo brings together two bodies of scholarship: Napoleonic history and Latin American independence. "The Emperor's Last Campaign" is a fascinating story, well told, and peopled with all sorts of improbable individuals and schemes that perhaps just missed coming to full fruition"--Jacket.